Monitoring of Mineral Elements and Heavy Metals in Camellia oleifera Seeds by ICP-MS - Hang, Ye; Ma, Jinlin; Chen, Guochen; Li, Kaixiang; Zhang, Naiyan (Asian Journal of Chemistry, 2010)
Concentrations of mineral elements Ca, K, Fe, Mn, Zn, Se, Mo, Mg and heavy metals Pb, Cd, Cu, Cr, Al and As in Camellia oleifera seeds were determined by inductively coupled-plasma mass spectrometry (ICP-MS). The results showed that there are many and much mineral elements in Camellia oleifera seeds, which is essential to human health. Camellia oleifera seeds contain little heavy metals. The harmful element Al is the highest why Camellia oleifera usually grow in southern red soil. The relative standard deviation (RSD) range from 1.87-4.78 % and the recovery range from 96.78-105.98 %. According to the concentration, Camellia oleifera seeds contain much mineral elements which is beneficial to human health as food material, but the concentration of aluminium is high, so we should remove aluminium when produce edible oil with Camellia oleifera seeds.